Comparative Evaluation of the Efficacy in Treating Children with Seasonal Allergic Rhinitis Using Antihistamine Combined with Ectoine Nasal Spray and Antihistamine Monotherapy: Results of an Open Randomized Study - N. V. Minaeva; D. M. Shiryaeva (Вопросы современной педиатрии)
Objective: Our aim was to evaluate the efficacy of an ectoine nasal spray in treating children with seasonal allergic rhinitis.Methods: An open randomized study of children aged 3–17 with the aggravation of early spring hay fever. All participants received oral antihistamine, and the children of the treatment group — oral antihistamine plus ectoine nasal spray. The symptoms of the disease and the amount of additional drug therapy were analyzed on the 1st, 10th and 21st day of treatment. Results: The group with patients who received an ectoine nasal spray (n = 24) showed a significant, if compared to the control group (n = 18), decrease in the severity of all symptoms of rhinitis — nasal congestion from the 14th day of treatment (p = 0.010), nasal discharge — from the 15th day of treatment (p = 0.036), nasal irritation and sneezing — from the 17th day of treatment (p = 0.020), as well as the symptoms of allergic conjunctivitis such as itchy eyes — from the 18th day of treatment (p = 0.020) and conjunctival hyperemia — from the 19th day of treatment (p = 0.040). The use of an ectoine nasal spray was accompanied by a decrease in the frequency of the assignment of drugs for the additional rhinitis treatment.Conclusion: An ectoine nasal spray in combination with antihistamines induces a more rapid relief of major symptoms of seasonal allergic rhinitis and allergic conjunctivitis in children, as well as reduces the need for additional medical treatment of the disease, if compared to the antihistamine monotherapy.